Naskah Adji's (Sentolo) : Kajian Filologi (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
Abstract Adji’s (Sentolo) manuscript is one of the primbon category manuscripts witch contains ruwatan mantras along with predictions if an earthquake or eclipse occurs in a certain month. The purpose of this study is to provide edits and translations of the AS text according to philological rules and to provide information on what spells exist in the AS text. The data used in this study is Adji’s (Sentolo). The data source is the Adji’s (Sentolo) manuscript with the code in the SK 165 catalog stored in the Sonobudoyo State Museum Library Unit II, Yogyakarta. The research method used is a philological reaserch method with a standard edition single manuscript editing method and a free translation method so that it is easily understood by readers. The result obtained from this study are in the form of valid text edits according to philological rules and text translations in Indonesian. The deepest spells in the AS text are divided into two parts. In the first part there are mantras such as gumbala geni, tunjung kuning, tulak tanggul, caraka balik, dunga srabat, and predictions in case of earthquakes and eclipses. In the second part there are bidding spells such as jaramaya or caraka balik, tulak tanggul, the difference lies in the pronunciation of spell used. Based on AS manuscript research that has been carried out philologically, in this study the results of edits and translations of the text were obtained and contained information about various kinds of ruwatan mantras. This research can be continued and become a reference for other sciences, such as linguistics, especially in stylistics. Keywords : Philology; Adji’s (Sentolo); Text Editing; Text Translation.